Comparison of anterior retraction and anchorage control between en masse retraction and two-step retraction: A randomized prospective clinical trial - Schneider, Patricia Pigato [UNESP]; Gandini Junior, Luiz Gonzaga [UNESP]; Monini, Andre da Costa; Pinto, Ary dos Santos [UNESP]; Kim, Ki Beom (E H Angle Education Research Foundation, Inc, 2019)
Objectives: The purpose of this two-arm parallel trial was to compare en masse (ER) and two-step retraction (TSR) during space closure. Materials and Methods: Forty-eight adult patients with bimaxillary protrusion who were planned for treatment with extraction of four first premolars were enrolled. All patients were randomly allocated in a 1: 1 ratio to either the ER (n = 24) group or the TSR (n = 24) group. The main outcome was the amount of posterior anchorage loss in the molars and the retraction of the incisors between ER and TSR; the difference in incisor and molar inclination was a secondary outcome. Lateral cephalometric radiographs and oblique cephalometric radiographs at 458 were taken before retraction (T1) and after space closure (T2). Cephalograms were digitized and superimposed on the anatomic best fit of the maxilla and mandible by one operator who was blinded to the treatment group. Results: Neither incisor nor molar crown movements showed any significant differences between the ER and TSR. There were no significant differences in the tipping of incisors and molars between the two groups. Conclusions: No significant differences existed in the amount of retraction of incisors and anchorage loss of molars between ER and TSR. Changes in incisor and molar tipping were similar, with the crowns showing more movement than the apex.
Keywords: En masse retraction; Two-step retraction; Anchorage loss; Retraction; Space closure; Orthodontics